Transforming Computer Science Educators Landscape Using the Greek School Network - Paraskevas, Michael; Zarouchas, Thomas (International Journal of Advanced Corporate Learning (iJAC), 2013)
This study presents the potential use of Greek School Network (GSN) to provide a robust and versatile e-learning course for computer science educators, in order to efficiently exploit advanced IT services, thus establishing a modern and attractive education environment in the Greek Society. For this reason, a time Scheduling and Tele-Education Platform (t-STEP) is introduced that efficiently compensates the growing needs on information and communication technologies and also provides the appropriate training framework to computer science educators in order to excel their technical proficiency